The causal relationship between fertility rate and economic growth: empirical evidence from Malaysia / Irlisuhayu Mohd Ramli ...[et al.] - Mohd Ramli, Irlisuhayu; Ahmad Khan, Hafizah Hammad; Samsi, Siti Muliana; Ahmad, Nabila (2019)
The declining trend of fertility rate across countries has raised concerns among economist since it could bring severe consequences on the long run economic growth. The current population trend in Malaysia which shows the country is moving towards the ageing country due to higher life expectancy and lower fertility rate indicate that the country will face a serious challenge in the future as they will be highly dependent on the elderly to support the labour market if the fertility rate continues to decline over time.